The Context of APEX - Universiti Sains Malaysia, Pejabat Naib Canselor (Universiti Sains Malaysia, 2013)
Universiti Sains Malaysia (USM) was selected to implement the Accelerated Programme for Excellence (APEX) in 2008. APEX is a fast track development programme to enable institutions of higher education to be recognised as world class entities. The programme aims to facilitate the university selected to be on an international level and also to motivate and help raise the level of excellence in higher education. The APEX programme was identified as one of the most critical initiatives to help transform Malaysian Higher Education.